(untitled) (Journal of Informatics Education and Research, 2025)
Adolescence is a time of transition characterised by changes in one’s physical, mental, emotional, and social characteristics. Because they affect confidence, relationships, and decision-making, self-esteem and social adjustment are essential for wellbeing. Identity and self-perception are shaped by puberty, peer pressure, and family support. While low self-esteem causes social disengagement and anxiety, high self-esteem promotes adaptation and resilience. Building relationships and navigating societal expectations are made possible by social adjustment. Self-esteem and adaptability are improved by techniques like mindfulness, positive self-talk, and conquering anxieties. Peer relationships, self-development, and supportive parents are essential for a smooth transition into adulthood.